Sexualita jako riziko? Sexuální výchova v českých kurikulárních dokumentech - Barbora Benešovská; Dagmar Krišová; Marcela Macháčková (Karolinum Press, 2024)
Formal sex education and its implementation in education have been increasingly debated in recent years. In the Czech Republic, the area came to the centre of public policy interest in early 2023, when, in response to several sexual harassment cases, former Minister of Education, Mr. Balaš, expressed the need to strengthen sex education in schools. With the ongoing revision of the national Framework Educational Programme and the awareness of the lack of research coverage in this area, we consider it appropriate to look at how sex education is framed in institutional documents in the Czech Republic today. We conduct a qualitative analysis of the Recommendation of the Ministry of Education for the Implementation of Sexuality Education in Primary Schools, selected school education programmes and minimum prevention programmes. We compare these with the principles, rationale and topics articulated in the Standards for Sexuality Education in Europe, which were developed to support the implementation of holistic sexuality education. We point out significant differences in the conceptualisation of the Czech documents, particularly the normative, biologizing and risk-oriented sex education. We see the untold potential for a quality approach to sex education, which takes into account the sexual subjectivity and uniqueness of adolescents' experience and the interactive nature of sexuality, which the Standards for Sexuality Education in Europe emphasize, in the areas of Education for Citizenship, Ethics Education or in Social and Personal Development.